Abnormal Uterine Bleeding: Clinical and Histopathological Correlation in a Tertiary-Care Cohort from Rajshahi - Khondokar Sehely Nasrin Lina; Salma Akter; Nilufar Sharmin (TAJ: Journal of Teachers Association, 2026)
Background: Abnormal uterine bleeding affects women across reproductive and postmenopausal life stages and may signal a spectrum extending from benign endometrial change to malignancy. Objective: This study evaluated the correlation between clinical presentation and histopathological findings in women with abnormal uterine bleeding. Methods: A cross-sectional analytical study was conducted in the Department of Gynecology and Obstetrics, Rajshahi Medical College Hospital, from July 2025 to June 2026, enrolling 156 women aged 18–65 years with abnormal uterine bleeding. Clinical variables, endometrial thickness, and histopathological diagnoses were extracted from case records and analysed using SPSS v26.0, with p